Diagnosis of communication in the project sector of a large mining company: a case study - Silva, Michael Júnio Paixão; Frossard, Gabriela Corrêa (Brazilian Journal of Production Engineering, 2024)
This work aims to contribute to improving processes in a large mining company in the central region of Minas Gerais. The work was structured using the case study method. A survey of management information was carried out on the main activities of the company’s project sector. The bibliographical research was based on existing agile methods, with special attention to Scrum, in addition to Communication Management concepts. Based on the case study, the research used a questionnaire in order to obtain qualitative data. After the analysis, an action plan was proposed to improve the communication scenario in the sector studied. The results identified showed that, although there are methods available for information management, internal communication is still flawed in some aspects, and improvements were suggested to be applied in the sector, presented at the end of the text in the 5W2H model.